Efektivitas Pembelajaran Kooperatif Dengan Permainan Dalam Matematika - Erawati, Ni Ketut; Suwarnisi, Ni Made (Jurnal Matematika; Vol 9 No 2 (2019)DO - 10.24843/JMAT.2019.v09.i02.p114, 2019)
The purpose of this study was to determine the effectiveness of the application of the STAD cooperative learning model combined with ice breaking in mathematics subjects on motivation and learning outcomes of student. This research is a quasi-experimental study using the non equivalent design group design. This design uses two sample groups selected with random sampling and randomized classes are already available. This research was conducted at SMK N 4 Denpasar with a population of 10th grade students consisting of 10 classes, then two classes were selected as samples.Data collection using questionnaires and essay test. Data analysis uses t-test for the first hypothesis and the second hypothesis while the third hypothesis analysis uses MANOVA. The results of the research show that the motivation and learning outcomes between the experimental group and the comparison group differed significantly, where better results were obtained in the experimental group ie the group that applied STAD cooperative learning with ice breaking. The results of this study indicate that cooperative learning innovations especially the STAD type combined with ice breaking as a game or pause in mathematics learning provide effective results in achieving student learning outcomes and motivation at a better level.